Students’ perception of innovative development of a society: comparative analysis of empirical data - Titarenko, Larissa G. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The purpose of the article is to describe the results of a students’ survey in Belarus conducted in 2023 using the similar tools to the previous study in 2022, and to provide a comparative analysis of their results. Both surveys were devoted to the problems of digital innovations implemented in the Belarusian society and the perception of these innovations by the students. An analysis of the results of the 2023 survey revealed some changes compared to the 2022 survey data. These changes are probably associated with a sharp (more than twofold) decrease in the number of students who studied remotely (fully or in part) during the current academic year. The comparison revealed the important role of distance learning as a factor that stimulated the students’ learning of new technologies, studying technical innovations and thereby improving their digital literacy. The return to traditional forms of education had made the students’ life easier (stress levels have decreased), but the growth of their digital culture has slowed down. The scientific significance of the study lies in demonstrating the dependence of the students’ perception of digital innovations in a society and in the higher education system on the degree of constant participation in digital learning activities, as well as on the level of routinisation of innovations in students’ lives.
Keywords: innovative development of society; digital transformation; online learning; digital technologies; students’ perception of digital innovations